SPIRIT extension and elaboration for n-of-1 trials: SPENT 2019 checklist. (27th February 2020) - Porcino, Antony J; Shamseer, Larissa; Chan, An-Wen; Kravitz, Richard L; Orkin, Aaron; Punja, Salima; Ravaud, Philippe; Schmid, Christopher H; Vohra, Sunita
Abstract : Randomised clinical trials are the preferred method for establishing average intervention effects for groups. Using key methodological elements of these trials, n-of-1 trials provide rigorous evidence of intervention effects for individuals. N-of-1 trials are particularly useful for situations where randomised clinical trials are not always feasible or appropriate, such as for individuals with rare diseases, comorbid conditions, or using concurrent treatments. N-of-1 trials enhance precision when intervention effects are heterogeneous between individuals. Here, we describe an extension to the SPIRIT (standard protocol items: recommendations for interventional trials) guideline, SPENT (SPIRIT extension for n-of-1 trials), to improve the completeness and transparency of n-of-1 trial protocols. SPENT is also aligned with the CONSORT (consolidated standards of reporting trials) extension for n-of-1 trials (CENT). The guideline development group followed the development strategy for reporting guidelines endorsed by the EQUATOR Network. SPENT began with a systematic review for n-of-1 protocol recommendations. After analysis to identify possible SPENT items, a three round Delphi process was implemented, with international participation involving researchers, patient advocates, and other stakeholders. This was followed by in-person meetings and email discussion of the SPENT group to achieve consensus. SPENT has 14 extension items specific to n-of-1 trials, a checklist for n-of-1 trial protocol abstracts, and additional guidance for eight SPIRIT items where trialists could encounter issues specific to n-of-1 trials. This paper describes the rationale and development process, and provides examples and explanations for each SPENT checklist item.